f'(x).... y=(e^x-e^-x)/(e^x+e^-x). I need the calculation work.
I'm not exactly sure what your asking for or what the question is? I assume your trying to solve for the derivative? Did you try plugging it into wolfram alpha an clicking on show steps? That always works. Well not always, but it defiantly well if interperting (e^x-e^-x)/(e^x+e^-x) this correctly to be the original functionposted by Lee
f(x) = (e^x - 1/e^x) / (e^x + 1/e^x))
how about multiplying each term by e^x to get
f(x) = (e^2x - 1)/(e^2x + 1)
f'(x) = [(e^2x + 1)(2e^2x) - (e^2x - 1)(2e^x)]/(e^2x + 1)^2
= 4e^(2x) / (e^2x + 1)^2
posted by Reiny